Prevention of Clostridium difficile Infection and Associated Diarrhea: An Unsolved Problem - Principi, Nicola (Microorganisms, 2020)
For many years, it has been known that Clostridium difficile (CD) is the primary cause of health-care-associated infectious diarrhea, afflicting approximately 1% of hospitalized patients. CD may be simply carried or lead to a mild disease, but in a relevant number of patients, it can cause a very severe, potentially fatal, disease. In this narrative review, the present possibilities of CD infection (CDI) prevention will be discussed. Interventions usually recommended for infection control and prevention can be effective in reducing CDI incidence. However, in order to overcome limitations of these measures and reduce the risk of new CDI episodes, novel strategies have been developed. As most of the cases of CDI follow antibiotic use, attempts to rationalize antibiotic prescriptions have been implemented. Moreover, to reconstitute normal gut microbiota composition and suppress CD colonization in patients given antimicrobial drugs, administration of probiotics has been suggested. Finally, active and passive immunization has been studied. Vaccines containing inactivated CD toxins or components of CD spores have been studied. Passive immunization with monoclonal antibodies against CD toxins or the administration of hyperimmune whey derived from colostrum or breast milk from immunized cows has been tried. However, most advanced methods have significant limitations as they cannot prevent colonization and development of primary CDI. Only the availability of vaccines able to face these problems can allow a resolutive approach to the total burden due to this pathogen.